The classical commentary : histories, practices, theory - Gibson, Roy K.; Kraus, Christina Shuttleworth, 1958- (Mnemosyne, bibliotheca classica Batava. Supplementum, 2002)
Written primarily by practising commentators, these papers examine the issues raised by the writing and reading of commentaries on classical Greek and Latin texts.